Optimal algorithms for preemptive two-agent scheduling on uniform parallel machines - Gu, Manzhan; Liu, Peihai; Lu, Xiwen (Theoretical computer science, 2024)
This paper studies two scheduling problems involving two agents A and B, where each agent has an independent set of jobs and all jobs are to be processed preemptively on uniform parallel machines. The aims of the two problems are to minimize the objective function value of agent A with the makespan of agent B not exceeding a threshold T. In the first problem, there are m machines and the objective function of agent A is the makespan. In the second problem, there are two machines and the objective function of agent A is the total completion time. For each of the two problems, we propose an optimal algorithm and obtain some extended results.